Allergy to the iodinated contrast media – the clinical and immunological aspects – a literature review (Journal of Medical Science, 2022)
Aim. The aim of this paper is to analyse and review the currently available evidence and research with regard to allergy to the iodinated contrast media, which still remains an important, albeit rare, clinical complication. Material and Methods. We performed our research using the PubMed search engine provided by the National Centre for Biotechnology Information, having inserted ‘iodinated contrast media’, ‘allergy’, ‘adverse reactions’ as the keywords. Results. Even though the modern iodinated contrast media are much safer than those used in the past, adverse reactions still occur in up to 1–3% of patients undergoing radiological procedures. Their range varies from skin changes, such as a macular rash, prurigo or urticarial, to the more severe multisystemic reactions including anaphylactic shock. The underlying mechanisms are still investigated and are not fully comprehended, although the most frequently accepted explanations include a systemic inflammatory reaction associated with increased histamine and tryptase levels, activation of memory T cells and both direct and indirect damage to the vascular epithelium. The significance of classic allergy tests has not yet been fully established. The associated known risk factors are of various character and researchers have come with different, occasionally contradicting results regarding patients’ age and gender, however, other factors have been more clearly described, and include concomitant conditions and medications. Conclusions. The aforementioned data emphasizes the importance of clinical aspects of allergy to the iodinated contrast media for every practicing physician, as more and more medical specialties benefit from the advantages of modern vascular imaging.